2021
DOI: 10.4274/mirt.galenos.2021.04934
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of <sup>18</sup>F-FDG/PET SUV<sub>max</sub>, SUV<sub>mean</sub>, MTV, and TLG with HIF-1α in Patients with Colorectal Cancer

Abstract: Objectives: Post-hypoxia hypoxia-inducible factor (HIF)-1α activation plays a vital role in colorectal cancer (CRC) angiogenesis. Although glucose metabolism is induced in some cancer types via HIF-1α, the prognostic significance of HIF-1α in CRC and its correlation with 18 fluorinefluorodeoxyglucose ( 18 F-FDG) uptake in positron emission tomography (PET) remain controversial. This study aims to investigate the association between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…These results suggested that SUVmax, as a prognostic factor, could reflect cancer immune microenvironment. Interestingly, SUVmax was also associated with tumor tissue hypoxia and angiogenesis, contributing to cancer progression [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that SUVmax, as a prognostic factor, could reflect cancer immune microenvironment. Interestingly, SUVmax was also associated with tumor tissue hypoxia and angiogenesis, contributing to cancer progression [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…MTV and TLG, which are a combination of volumetric and metabolic parameters, may be utilized in metabolic analyses of radiotracer activity, reflecting both properties of the tumor tissues. These parameters were also related to angiogenesis [ 41 ] and cancer immunity [ 42 ]. Taken these considerations, the above parameters in 18F PDF PET were associated to glucose intake, which regards cancer metabolism activity, tumor microenvironment, and immunity.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between HIF-1α and FDG-PET/CT parameters is controversial. Kaymak et al (22) revealed no significant association between HIF-1α and SUVmax in colorectal carcinoma probably because of the heterogeneity of the oxygen situation within the tumor.…”
Section: Univariate Analysis Multivariate Analysismentioning
confidence: 98%